Peran Nyanyian Jemaat Dalam Penguatan Moderasi Beragama di GKE Imanuel Kuala Pembuang - Wirawan, Aprianto (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
The research background originated from the search for field results regarding religious moderation with the study of musical performances in GKE Imanuel Kuala Pembuang, Seruyan, Kalimantan Tengah. Purpose of this research is to describe the challenges, the role of congregational singing in strengthening religious moderation in GKE Imanuel Kuala Pembuang Resort GKE Seruyan Hilir. Qualitative research method used an interview technique with church members, pastors of GKE Seruyan Hilir congregation and correlated it with religious moderation. The results of this study found that church singing has an important role in shaping the character of the people because church singing is one of the means in conveying God's Word. Church singing is a tangible form of teaching as well as proclaiming the gospel to the world where the invitation to moderate life can be found through lyrics, music and singing.